2012
DOI: 10.3892/ol.2012.622
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal metastasis of carcinoid tumors: Two case reports and review of the literature

Abstract: Abstract. Carcinoid tumors are neuroendocrine neoplasms derived from enterochromaffin cells. Skeletal metastases from carcinoid tumors are considered to be extremely rare. In this study, we present two cases of carcinoid tumors that metastasized to the bone. Furthermore, we review 50 published case reports and reveal the features of skeletal metastasis of carcinoid tumors. The first case involved a 59-year-old man with a history of multiple metastases of a lung carcinoid tumor. The patient complained of back p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 27 publications
1
22
0
Order By: Relevance
“…Carcinoid tumors were of bronchial (n = 9) and nonpulmonary origin (n = 17)-of which CNS (n = 2) and thymus (n = 3)-, and 4 patients had carcinoid tumors of unknown primary, whereas in 7 patients, the origin was not specified. [16][17][18][19][20][21][22][23][24][26][27][28][29][30][31][32]34,35,37,38,43 Only 6 pNET cases, including ours, of malignant spinal cord compression have been reported in the literature, 25,33,36,40,41 with two of them due to "functional" pNETs (ie, glucagonoma, gastrinoma). As far as we know, our case is the first ever reported of a pNETwith an "intradural" metastasis to the spinal cord, and we only found the following 4 other cases of spinal intradural NET metastases: 2 thymic carcinoids, 28,35 1 lung atypical carcinoid, 18 and a probable primary atypical carcinoid of the CNS.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Carcinoid tumors were of bronchial (n = 9) and nonpulmonary origin (n = 17)-of which CNS (n = 2) and thymus (n = 3)-, and 4 patients had carcinoid tumors of unknown primary, whereas in 7 patients, the origin was not specified. [16][17][18][19][20][21][22][23][24][26][27][28][29][30][31][32]34,35,37,38,43 Only 6 pNET cases, including ours, of malignant spinal cord compression have been reported in the literature, 25,33,36,40,41 with two of them due to "functional" pNETs (ie, glucagonoma, gastrinoma). As far as we know, our case is the first ever reported of a pNETwith an "intradural" metastasis to the spinal cord, and we only found the following 4 other cases of spinal intradural NET metastases: 2 thymic carcinoids, 28,35 1 lung atypical carcinoid, 18 and a probable primary atypical carcinoid of the CNS.…”
Section: Discussionmentioning
confidence: 98%
“…42 Most of the cases (n = 35) are in fact extradural spinal cord compressions due to vertebral metastases with an epidural soft tissue component. 16,19,[21][22][23][24][25][26]29,[32][33][34][35][36][37][38][39]41,43 Reported cases include carcinoid tumors (n = 36), pNET (n = 6), and NETs of unknown primary (n = 3). Carcinoid tumors were of bronchial (n = 9) and nonpulmonary origin (n = 17)-of which CNS (n = 2) and thymus (n = 3)-, and 4 patients had carcinoid tumors of unknown primary, whereas in 7 patients, the origin was not specified.…”
Section: Discussionmentioning
confidence: 98%
“…Although skeletal involvement in carcinoid patients is rarely considered symptomatic [43,44], we found that bone pain and/or neurologic symptoms related to spinal cord or nerve root compression were present in 55 and 22% of the overall cohort, respectively. Of note, SREs occurred in 24% of the patients and were diagnosed at borderline increased frequency in patients with metachronous bone metastases (p = 0.08), probably as a consequence of their delayed detection.…”
Section: Discussionmentioning
confidence: 80%
“…However, bone metastases have been historically regarded as rare complications of NETs and their clinical relevance has been frequently confined to symptomatic patients [43]. Therefore, whether or not skeletal metastases should be systematically investigated in patients with NETs, who might be at increased risk of morbidity from bone metastases, whether markers of malignant osteoclastogenesis are useful in clinical practice, and what is the management of bone-metastatic NETs are still unknown topics since international guidelines do not suggest evidence-based recommendations in this regard [4,44].…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports show that patients with skeletal metastases from carcinoid tumors do not always complain of pain. 14,15 Similarly, only 44 % of patients herein underwent localized therapy of their symptomatic bone metastases. Most patients in our study were treated with radiotherapy (40 %).…”
Section: Discussionmentioning
confidence: 97%